(untitled) (Al-Academy, 2026)
This research explores human perception of the innate connection with the physical environment and its topographic elements. Topography has come to play a central role in shaping interior spaces, especially in light of current environmental transformations and the growing challenges related to sustainability. Accordingly, it has become essential to integrate topographic elements into interior design—both in form and function—through approaches that achieve a balance between aesthetics, utility, and sustainability. Thus, the research problem was formulated through the following question: How does integrating topographic elements into interior design enhance the aesthetic and environmental performance of interior spaces in light of sustainable design approaches? The research aimed to uncover how topographic elements are embodied in interior design, both functionally and aesthetically, and to analyze the extent of their contribution to achieving sustainability. The theoretical framework included two sections. The first section addressed the conceptual dimension of topography and its relation to sustainability, while the second section focused on topographical representations in sustainable interior design. The study developed a set of indicators based on the theoretical framework, which were used to construct the analysis form. The research adopted a descriptive-analytical methodology to arrive at a set of findings and conclusions, most notably: Topography constitutes an effective design element that goes beyond formal aspects to functional and environmental performance. When consciously employed, it can create spatial integration between design and site, providing climate-responsive solutions that reduce energy consumption—provided it is based on a deep understanding of the land’s nature, rather than superficial or symbolic application